INCREASING QUALITY OF EXPORT BLUE CRAB MEAT AT HOME INDUSTRY (UKM) FISHERIES MANUFACTURED IN PASURUAN - Mimit Primyastanto (Journal of Innovation and Applied Technology, 2017)
Pasuruan is a fisheries potential district. One of the potential product is blue crab. Blue crab is an export commodity in United States and Japan. Now, Demands of blue crab has been increased from buyer. From this, needed improvement on technical development, fast and precise handling for stabilizing quality of blue crab. This project is planning on two home industries, Home industry (UD) Surya Abadi and Home Industry (UD) Sari Laut at Kisik and Pasinan Village. This project was doing with spacious survey, interview, and observation. The problems on two home industries is sanitation and hygiene was not appropriating with export standars and conventional manufacturing. At Now, this project give an effectiveness technology such as crab cold box, ice cruiser, shelters meat blue crab and trolleys. From this technology, expectable that home industries can produce the best blue crab from long durability, best sanitier and hygiene, increasing markets area in United States, Japan to new markets such as Korea, China, Taiwan, and can increase the home industries’s  profit. Furthermore, home industries can manufacturing blue crab with hygienic, sanitary, and live with export standart where have a correlation with effectiveness technology. Furthermore, home industries must to make the good accounting for knowing the profit and profitability of manufactures. Not only that, government can build and increase export market to all countries where have commertial relations with Indonesia.